Perspektif Dibalik Perilaku Living Together di Kalangan Mahasiswa di Kota Semarang - Aprilian Dani Bagus Setiawan; Putri Gevira; Rauly Sijabat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the perspectives behind cohabitation behavior among students in Semarang City. This study uses a qualitative approach with a phenomenological method. The results of the study can be drawn several conclusions as follows: (a) Subjective Perspective and Meaning: Student actors interpret cohabitation not merely as a deviation, but as a form of "compatibility test" or trial marriage to understand the character of the partner before a long-term commitment. There is a construction of meaning that places personal autonomy and efficiency above traditional norms; (b) Primary Motivation: There is a mutually reinforcing dichotomy of motivations, namely emotional-psychological motivation to gain closeness and intensive affection3, and pragmatic-economic motivation in the form of saving on living costs (such as rent and food) through shared burdens; and (c) Dynamics and Risks: Cohabitation is characterized by a complex adaptation phase, where relationships often become more vulnerable due to conflicts of daily habits and loss of privacy5555. The most obvious risks include decreased academic performance (delay in graduation)6 as well as moral burdens and social pressures that require them to carry out strategies of hiding their identity ("acting") in the community environment